Mitchell, Barbara. Photograph of Barbara Mitchell and Anita Druken from Barbara Mitchell's personal photograph collection. - Jarvis, Dale
Barbara Mitchell and Anita Druken in matching dresses made by their mother in front of Dodge truck.